TaRCoS: Providing a Combat Simulation Tool for Tabletop Role-Playing Games - Silva Junior, Alberto Manoel dos Santos; Sarinho, Victor Travassos (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais Estendidos do XX Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames_estendido.2021.19665, 2021)
Role-Playing Game (RPG) is a game where players pretend to be a character acting in an environment and story created by the narrator and the players. During a tabletop RPG game, there are events, usually battles, in which players waste a lot of time to get a result for the action they choose to perform. To optimize this aspect, this paper presents the Tabletop RPG Combat Simulator (TaRCoS), a software tool able to perform tabletop RPG combat and show the winner of modeled matches in a tabletop RPG system. It eliminates the expenditure of time to get a battle result, such as the excessive calculations of dice rolls, and provides data for balancing purposes of specific characters during an initial combat configuration for modeled matches. As a result, TaRCoS improves the dynamics of playing tabletop RPG games, avoiding unnecessary efforts to define battle results and allowing players and narrators to be concerned with the description of the scene, the construction of desired game elements, and the player immersion in an amazing game story.